Influence of sound and light combined conditions in urban environments on residents’ tolerance limits in pre sleep state - Yu, Yue; Feng, Danya; Zhang, Xin; Kang, Jian (Frontiers in Psychology, 2023)
To determine the sound and light combined conditions pollution in urban residential environments at night, this paper comprehensively evaluates cross-visual and auditory sensory channels in the laboratory. Experimental variables include extremum and gradient, and the working state of the participants was determined and verified. A subjective evaluation experiment on 18 combined conditions was carried out by synthesizing real-world data. Results from the sound and light combined conditions experiment show that there are significant differences in the tolerance limits of participants to different content sound variables (p = 0.000 < 0.05, p = 0.033 < 0.05, p = 0.002 < 0.05). Among them, the traffic noise (p = 0.000 < 0.05) has the greatest impact on the tolerance limits of people, followed by birdsong (p = 0.033 < 0.05) and human voice (p = 0.002 < 0.05). There is no difference in the tolerance limits of light pollution (p = 0.288 > 0.05, p = 0.122 > 0.05, p = 0.146 > 0.05) at different color temperatures. The tolerance limits of participants will not be reduced due to the superposition of two interference variables: sound pollution and light pollution. Adding light pollution to sound pollution can increase the tolerance limits of participants, while adding sound pollution to light pollution has no significant effect on the tolerance limits. The study also found that adding light with different color temperatures to the human voice can increase participants’ tolerance limit to human voice (1% -2%), indicating that visual elements can change individuals’ perception of sound. In addition, the physiological and psychological differences between participants may affect the performance differences of individual participants in sound and light combined conditions.